Anti-inflammatory and anti-diabetic effects of brown seaweeds in high-fat diet-induced obese mice - Oh, Ji-Hyun (Nutr Res Pract, 2016)
BACKGROUND/OBJECTIVES: Seaweeds have been reported to have various health beneficial effects. In this study, we investigated the potential anti-obesity and anti-inflammatory effects of four types of domestic brown seaweeds in a high-fat diet-induced obese mouse model and bone marrow-derived macrophages (BMDM). MATERIALS/METHODS: Male C57BL/6N mice were fed low-fat diet (LFD), high-fat diet (HFD) or HFD containing Undaria Pinnatifida, HFD containing Laminaria Japonica (LJ), HFD containing Sargassum Fulvellum, or HFD containing Hizikia Fusiforme (HF) for 16 weeks. RESULTS: Brown seaweed supplementation did not affect long-term HFD-associated changes in body weight or adiposity, although mice fed HFD + LJ or HFD + HF gained slightly less body weight compared with those fed HFD at the beginning of feeding. Despite being obese, mice fed HFD + LJ appeared to show improved insulin sensitivity compared to mice fed HFD. Consistently, we observed significantly reduced blood glucose concentrations in mice fed HFD + LJ compared with those of mice fed HFD. Although no significant differences in adipocyte size were detected among the HFD-fed groups, consumption of seaweeds decreased formation of HFD-induced crown-like structures in gonadal adipose tissue as well as plasma inflammatory cytokines. BMDM from mice fed HFDs with seaweeds showed differential regulation of pro-inflammatory cytokines such as IL-1β and IL-6 compared with BMDM from mice fed HFD by LPS stimulation. CONCLUSION: Although seaweed consumption did not prevent long-term HFD-induced obesity in C57BL/6N mice, it reduced insulin resistance (IR) and circulation of pro-inflammatory cytokines. Therefore, seaweeds may ameliorate systemic inflammation and IR in obesity partially due to inhibition of inflammatory signaling in adipose tissue cells as well as bone marrow-derived immune cells.